The impact of a demand-side sanitation and hygiene promotion intervention on sustained behavior change and health in Amhara, Ethiopia: A cluster-randomized trial - Matthew C. Freeman; Maryann G. Delea; Jedidiah S. Snyder; Joshua V. Garn; Mulusew Belew; Bethany A. Caruso; Thomas F. Clasen; Gloria D. Sclar; Yihenew Tesfaye; Mulat Woreta; Kassahun Zewudie; Abebe Gebremariam Gobezayehu (PLOS Global Public Health, 2022)
Behaviors related to water, sanitation, and hygiene (WASH) are key drivers of infectious disease transmission, and experiences of WASH are potential influencers of mental well-being. Important knowledge gaps exist related to the content and delivery of effective WASH programs and their associated health impacts, particularly within the contexts of government programs implemented at scale. We developed and tested a demand-side intervention called Andilaye, which aimed to change behaviors related to sanitation, personal hygiene, and household environmental sanitation. This theory-informed intervention was delivered through the existing Ethiopian Health Extension Programme (HEP). It was a multilevel intervention with a catalyzing event at the community level and behavior change activities at group and household levels. We randomly selected and assigned 50 kebeles (sub-districts) from three woredas (districts), half to receive the Andilaye intervention, and half the standard of care sanitation and hygiene programming (i.e., community-led total sanitation and hygiene [CLTSH]). We collected data on WASH access, behavioral outcomes, and mental well-being. A total of 1,589 households were enrolled into the study at baseline; 1,472 households (94%) participated in an endline assessment two years after baseline, and approximately 14 months after the initiation of a multi-level intervention. The intervention did not improve construction of latrines (prevalence ratio [PR]: 0.99; 95% CI: 0.82, 1.21) or handwashing stations with water (PR: 0.96; 95% CI: 0.72, 1.26), or the removal of animal feces from the compound (PR: 1.10; 95% CI: 0.95, 1.28). Nor did it impact anxiety (PR: 0.90; 95% CI: 0.72, 1.11), depression (PR: 0.83; 95% CI: 0.64, 1.07), emotional distress (PR: 0.86; 95% CI: 0.67, 1.09) or well-being (PR: 0.90; 95% CI: 0.74, 1.10) scores. We report limited impact of the intervention, as delivered, on changes in behavior and mental well-being. The effectiveness of the intervention was limited by poor intervention fidelity. While sanitation and hygiene improvements have been documented in Ethiopia, behavioral slippage, or regression to unimproved practices, in communities previously declared open defecation free is widespread. Evidence from this trial may help address knowledge gaps related to challenges associated with scalable alternatives to CLTSH and inform sanitation and hygiene programming and policy in Ethiopia and beyond. Trial registration: This trial was registered with clinicaltrials.gov (NCT03075436) on March 9, 2017.